Procurement Selection Practices in Post Disaster Project Management - A Case Study in Banda Aceh, Indonesia - Bakar, Abu Hassan Abu; Osman, Omar; Bulba, Alfa Taras (2009)
On the 26 December 2004, a great 9.2 earthquake jolted Aceh, Indonesia, followed up by an atrocious tsunami minutes later that wipe out some 200,000 lives in Aceh and thousands more across neighbouring countries. Millions of dollars worth of properties have been damaged and completely destroyed. Billions of dollars poured in, involving many Non-governmental organizations (NGOs) world wide to help out rebuilt affected areas.